Nonaqueous electrolyte secondary battery

By introducing specific elements combinations into the positive electrode active substance of the lithium-ion battery and using silicon-containing materials in the negative electrode, the problem of the capacity of the lithium-ion battery in the charge and discharge cycle is solved, and the charge and discharge cycle characteristics of the battery are significantly improved.

CN119895608APending Publication Date: 2025-04-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380067231.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-08-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing non-aqueous electrolyte secondary batteries such as lithium-ion batteries are prone to decrease capacity during the charge and discharge cycle, and the charge and discharge cycle characteristics of the positive electrode have not been effectively improved.

Method used

The group selected from Ca and Sr and the group selected from W, Mo, Ti, Si, Nb and Zr are present at the primary particle interface inside the secondary particles of the positive electrode active material, and a silicon-containing material is used as the active material in the negative electrode to suppress the decrease in capacity and improve the charge and discharge cycle characteristics.

Benefits of technology

It significantly suppresses the capacity of the battery during charging and discharging, improves the charge and discharging cycle characteristics, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895608A_ABST
    Figure CN119895608A_ABST
Patent Text Reader

Abstract

In a nonaqueous electrolyte secondary battery (10), which is an example of an embodiment, a positive electrode (11) contains, as a positive electrode active material, a lithium transition metal composite oxide having a layered structure and containing at least 75 mol% of Ni with respect to the total molar amount of metal elements other than Li. The lithium transition metal composite oxide is a secondary particle formed by aggregating primary particles, and at least one element selected from the group consisting of Ca and Sr and at least one element selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr are present at the interface between the primary particles inside the secondary particle. The negative electrode (12) contains a silicon-containing material as a negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion batteries have been widely used in applications such as automotive applications and power storage applications that require high capacity, high durability, and rapid charge and discharge performance. For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery comprising SiO x The silicon-containing material shown in (0.5≤x≤1.6) is used as the negative electrode active material, contains propylene carbonate and diethyl carbonate as the solvent of the electrolyte, and contains LiBF4 as the salt of the electrolyte. In addition, Patent Document 1 records that a good SEI (Solid Electrolyte Interphase) film is formed on the negative electrode.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-143642 Summary of the invention

[0006] Generally, repeated charge and discharge of non-aqueous electrolyte secondary batteries such as lithium-ion batteries will lead to a decrease in capacity, and it is an important technical issue to suppress the degree of this capacity decrease. It should be noted that in the non-aqueous electrolyte secondary battery of Patent Document 1, the improvement of the positive electrode is not considered, and there is still room for improvement in the improvement of the charge and discharge cycle characteristics.

[0007] A secondary battery as one embodiment of the present disclosure is a non-aqueous electrolyte secondary battery having a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode contains a lithium transition metal composite oxide as a positive electrode active material, the lithium transition metal composite oxide having a layered structure and containing 75 mol% or more of Ni relative to the total molar amount of metal elements other than Li. The lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles, at the interface between primary particles inside the secondary particle, there is at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the negative electrode contains a silicon-containing material as a negative electrode active material.

[0008] The nonaqueous electrolyte secondary battery according to the present disclosure has a small decrease in capacity accompanying charge and discharge and is excellent in charge and discharge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a diagram schematically showing an axial cross section of a nonaqueous electrolyte secondary battery (cylindrical battery) as an example of an embodiment. DETAILED DESCRIPTION

[0010] The present inventors have discovered that by providing at least one species selected from the group consisting of Ca and Sr and at least one species selected from the group consisting of W, Mo, Ti, Si, Nb and Zr at the interfaces between the primary particles inside the secondary particles of the positive electrode active material, and by using at least a silicon-containing material as the negative electrode active material, the capacity decrease accompanying the charging and discharging of the battery is particularly suppressed.

[0011] In the non-aqueous electrolyte secondary battery disclosed herein, although the highly reducing ions generated by oxidative decomposition on the negative electrode containing the silicon-containing material are believed to increase the side reaction on the positive electrode, it is assumed that the specific elements such as Ca and Sr present on the surface of the primary particles of the positive electrode active material will significantly inhibit the side reaction. As a result, for example, the resistance increase in the positive electrode and the dissolution of the transition metal are inhibited, and the charge and discharge cycle characteristics are significantly improved.

[0012] In addition, when using a positive electrode active material with a high Ni content, especially in a high SOC (State Of Charge) state, a large amount of highly reactive Ni is present on the particle surface. 4+ , so it is easy to have side reactions with the electrolyte, and the deposition of decomposed products and the dissolution of transition metals may occur at the positive electrode. In this regard, it is also possible to effectively suppress side reactions and reduce the reaction resistance from the positive electrode by making specific elements such as Ca and Sr exist on the surface of the primary particles of the positive electrode active material.

[0013] Hereinafter, an example of an embodiment of a nonaqueous electrolyte secondary battery according to the present disclosure will be described in detail with reference to the drawings. It should be noted that a form in which each component of a plurality of embodiments and modifications described below is selectively combined is also included in the scope of the present disclosure.

[0014] In the embodiment described below, a cylindrical battery 10 in which a wound electrode body 14 is contained in an outer can 16 with a bottomed cylindrical shape is exemplified, but the outer body of the battery is not limited to a cylindrical outer can. As other embodiments of the non-aqueous electrolyte secondary battery involved in the present disclosure, a square battery with a square outer can, a coin-shaped battery with a coin-shaped outer can, and a bag-type battery with an outer body composed of a laminate sheet including a metal layer and a resin layer can be listed. In addition, the electrode body is not limited to a wound type, and can also be a stacked electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators.

[0015] Figure 1 1 is a cross-sectional view of a cylindrical battery 10 as an example of an embodiment. Figure 1As shown, the cylindrical battery 10 includes a wound electrode body 14, an electrolyte, and an outer can 16 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for the convenience of explanation, the sealing body 17 side of the battery is set as the upper side, and the tank bottom side of the outer can 16 is set as the lower side.

[0016] The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolyte), but may also be a solid electrolyte. In the present embodiment, a non-aqueous electrolyte is used. The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may, for example, use esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof may be cited. The non-aqueous solvent may contain a halogen substitute (e.g., fluoroethylene carbonate, etc.) formed by replacing at least a portion of hydrogen in these solvents with halogen atoms such as fluorine. The electrolyte salt may, for example, use a lithium salt such as LiPF6.

[0017] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, which are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of sandwiching the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0018] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 becomes the negative terminal.

[0019] A sealing gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16 so that a part of the side portion bulges inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumference of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end portion of the outer can 16 that is closely fitted with the sealing body 17.

[0020] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating component 25, an upper valve body 26, and a lid 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating component 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heating, the lower valve body 24 is deformed and broken to push the upper valve body 26 to the lid 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the lid 27.

[0021] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 , in particular, the positive electrode active material constituting the positive electrode 11 and the negative electrode active material constituting the negative electrode 12 will be described in detail.

[0022] [positive electrode]

[0023] The positive electrode 11 has a positive electrode core 30 and a positive electrode mixture layer 31 disposed on the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film having the metal disposed on the surface, or the like. The positive electrode mixture layer 31 contains a positive electrode active material, a binder, and a conductive additive, and is preferably disposed on both surfaces of the positive electrode core 30 except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by coating a positive electrode mixture slurry containing a positive electrode active material, a binder, and a conductive additive on the surface of the positive electrode core 30, drying the coating, and then compressing the coating to form the positive electrode mixture layer 31 on both surfaces of the positive electrode core 30.

[0024] As the conductive aid contained in the positive electrode mixture layer 31, carbon black such as acetylene black and Ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be listed. As the binder contained in the positive electrode mixture layer 31, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be listed. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0025] The positive electrode 11 includes a lithium transition metal composite oxide as a positive electrode active material, the lithium transition metal composite oxide having a layered structure and containing 75 mol% or more of Ni relative to the total molar amount of metal elements other than Li. As described in detail later, the lithium transition metal composite oxide is a secondary particle formed by the aggregation of primary particles. In addition, at the interface between the primary particles inside the secondary particles, there is at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0026] The positive electrode active material may have the above-mentioned lithium transition metal composite oxide (hereinafter referred to as "composite oxide (Z)") as a main component, or may be substantially composed of only the composite oxide (Z). It should be noted that, within the scope of the purpose of the present disclosure, the positive electrode active material may contain composite oxides or other compounds other than the composite oxide (Z). The content of the composite oxide (Z) is preferably 50% by mass or more of the total mass of the positive electrode active material, and may also be 70% by mass or more, 80% by mass or more, or substantially 100% by mass.

[0027] The composite oxide (Z) has, for example, a layered rock salt structure. Examples of the layered rock salt structure include a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, and the like. Among them, from the perspective of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred.

[0028] The composite oxide (Z) is a secondary particle formed by the aggregation of primary particles. The volume-based median particle size (D50) of the composite oxide (Z) is, for example, greater than 3 μm and less than 30 μm, preferably greater than 5 μm and less than 25 μm. Since the composite oxide (Z) is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size when the cumulative frequency reaches 50% from the side with a smaller particle size in the volume-based particle size distribution, also known as the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac Bell) and water as a dispersion medium. In addition, the particle size distribution of the positive electrode active material can be measured using an image-based particle size distribution measuring device (e.g., CAMSIZER X2 manufactured by Microtrac Bell) and water as a dispersion medium.

[0029] The average particle size of the primary particles constituting the composite oxide (Z) is, for example, 0.02 μm or more and 1 μm or less, preferably 0.05 μm or more and 0.8 μm or less. The average particle size of the primary particles is obtained as follows: a cross section of the secondary particles is photographed using a scanning electron microscope (SEM), the diameter of 100 circumscribed circles of the primary particles extracted by analyzing the SEM image is measured, and the measured values ​​are averaged for calculation. The cross section of the secondary particles can be prepared by a cross section polishing (CP) method.

[0030] For example, the composite oxide (Z) is of the general formula Li x Ni a Co b Mn c Al d M1 e M2 f O 2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. The content of the elements in the composite oxide (Z) can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron beam microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).

[0031] The composite oxide (Z) preferably contains Ni in an amount of 75 mol% or more relative to the total molar number of metal elements other than Li. By setting the Ni content to 75 mol% or more, a high-capacity battery can be obtained, and the effect of adding the above-mentioned metal elements M1 and M2 can be made more significant. That is, it can be considered that when a composite oxide (Z) with a high Ni content is used as a positive electrode active material, although a large amount of highly reactive Ni is present on the particle surface, 4+ However, due to the effects of metal elements M1 and M2, Ni 4+ The content of Ni may be 80 mol% or more, or 85 mol% or more relative to the total molar number of metal elements other than Li. The upper limit of the content of Ni is, for example, 95 mol%.

[0032] The composite oxide (Z) preferably further contains at least one selected from the group consisting of Mn and Co. As a preferred example of the composite oxide (Z), a lithium nickel composite oxide containing Mn, a lithium nickel composite oxide containing Mn and Co, or a lithium nickel composite oxide containing Co and Al can be cited. When the composite oxide (Z) contains Mn, the content of Mn is preferably 1 mol% or more and 25 mol% or less relative to the total molar number of metal elements other than Li, and more preferably 5 mol% or more and 20 mol% or less. In this case, it is easy to take into account both high capacity and high durability of the battery.

[0033] When the composite oxide contains Co, the content of Co is preferably 1 mol% or more and 15 mol% or less relative to the total molar number of metal elements other than Li, and more preferably 2 mol% or more and 7 mol% or less. In this case, it is easy to take into account both high capacity and high durability while suppressing material costs. When the composite oxide (Z) contains Al, the content of Al is, for example, 0.1 mol% or more and 5 mol% or less relative to the total molar number of metal elements other than Li.

[0034] The composite oxide (Z) also contains metal elements M1 and metal elements M2 as essential components. As described above, the metal element M1 is at least one element selected from the group consisting of Ca and Sr, and the metal element M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. It can be considered that by adding a small amount of M1 and M2 to the composite oxide (Z), side reactions can be suppressed, the reaction resistance from the positive electrode can be reduced, and the charge and discharge cycle characteristics can be effectively improved. It should be noted that if only one of M1 and M2 is added, a sufficient effect cannot be obtained.

[0035] The metal element M1 is present at least inside the secondary particles of the composite oxide (Z) at the interface between the primary particles, for example, it is present at a high density on the surface relative to the inside of the primary particles. The M1 present on the surface of the primary particles can be confirmed by TEM-EDX and STEM-EDX. M1 is present at the interface between the primary particles, for example, in a uniformly dispersed state. It should be noted that M1 can also be fixed to the surface of the secondary particles (the surface of the primary particles present on the surface of the secondary particles).

[0036] Even a very small amount of the metal element M1 is effective, but the lower limit of its content is preferably 0.05 mol%, more preferably 0.1 mol%, relative to the total molar number of metal elements other than Li in the composite oxide (Z). In addition, the content of M1 is preferably less than 1 mol% relative to the total molar number of metal elements other than Li. Even if more than 1 mol% of M1 is added, the improvement effect of the cycle characteristics is small, or the cycle characteristics are deteriorated. Adding more than 1 mol% of M1, for example, will lead to problems such as increased resistance and decreased charging capacity.

[0037] The content of the metal element M1 is preferably 0.05 mol% to 1 mol%, more preferably 0.1 mol% to 0.7 mol% or 0.2 mol% to 0.5 mol%. When Ca and Sr are added as M1, the total of their contents is preferably within this range.

[0038] Even if the metal element M2 is very small, it is effective, but the lower limit of its content is preferably 0.05 mol%, more preferably 0.1 mol%, relative to the total molar number of metal elements other than Li in the composite oxide (Z). In addition, the content of M2 can be the same as the content of M1 or higher than the content of M1, and is preferably less than 3 mol% relative to the total molar number of metal elements other than Li. Even if more than 3 mol% of M2 is added, the improvement effect of the cycle characteristics is small, or the cycle characteristics are deteriorated. In addition, adding more than 3 mol% of M2, for example, will lead to problems such as increased resistance and decreased charging capacity.

[0039] The content of the metal element M2 is, for example, lower than the content of Mn and higher than the content of M1. An example of a preferred content of M2 is 0.05 mol% or more and 1 mol%, more preferably 0.2 mol% or more and 0.8 mol% or less or 0.3 mol% or more and 0.7 mol% or less. When two or more elements are added as M2, it is preferred that the sum of their contents is within this range.

[0040] As described above, the metal element M2 is at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. All of these elements may be added to the composite oxide (Z), but preferably three or less elements are added. Among them, W, Ti, Nb and Zr are preferred. When two types of M2 are added, Nb and Zr, Nb and Ti, Nb and W, W and Ti, and W and Zr can be listed as preferred combinations of M2.

[0041] Metal element M2 is present at the interface between primary particles, for example, in the secondary particles of the composite oxide (Z), similarly to metal element M1, and is present at a higher density on the surface than in the primary particles. It should be noted that M2 can form a solid solution with other metal elements such as Ni. The solid solution amount of M2 can be confirmed by an inductively coupled plasma emission spectrometer (ICP-AES) or energy dispersive X-ray spectroscopy (EDS).

[0042] At the interface between primary particles inside the secondary particles of the composite oxide (Z), for example, a particle of the general formula M1 is fixed. α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr. In this case, M1 and M2 are contained in the same compound.

[0043] At least one compound selected from the group consisting of the following first compound, second compound and third compound may be fixed to the surface of the primary particle of the composite oxide (Z). An example of the third compound is the above-mentioned general formula M1 α M2 β O γ The compounds shown.

[0044] First compound: a compound containing at least one selected from the group consisting of Ca and Sr

[0045] Second compound: a compound containing at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr

[0046] Third compound: a compound containing at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb, and Zr

[0047] It should be noted that the composite oxide (Z) may contain other elements besides Li, Ni, Co, Mn, Al, M1, M2, and O. Examples of such other elements include Cu, Mg, Na, K, Ba, Fe, B, P, and S. When other elements are contained, their content is preferably 1 mol% or less relative to the total molar number of metal elements except Li.

[0048] The composite oxide (Z) can be synthesized, for example, by mixing and calcining an oxide containing at least Ni, preferably other metal elements such as Mn, Co, and Al, an M1 raw material, an M2 raw material, and a Li raw material. The composite oxide (Z) is obtained by crushing the calcined product and washing it with water. It should be noted that the water washing step can also be omitted. As an example of a Li raw material, Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, LiF, etc. can be listed. The oxide containing Ni and the like and the Li raw material are preferably mixed at a ratio of 1:0.98 to 1:1.12 in the molar ratio of the total amount of metal elements other than Li in the oxide to Li in the Li raw material.

[0049] Examples of M1 raw materials include Ca(OH)2, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, CaO, CaCO3, CaSO4, and Ca(NO3). 2、 CaCl2, CaAlO4, Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc. Examples of M2 raw materials include Nb2O5, Nb2O5·nH2O, WO3, Li2WO4, TiO2, Ti(OH)4, ZrO2, Zr(OH)4, MoO3, Li2MoO4, SiO, SiO2, etc.

[0050] The calcination process of the above-mentioned mixture is, for example, a multi-stage calcination process including at least a first calcination process and a second calcination process having a temperature higher than that of the first calcination process. In addition, the calcination of the mixture is carried out under an oxygen atmosphere, and at this time, for example, the oxygen concentration is set to be 85% or more. The preferred first calcination temperature varies depending on the composition of the mixture, but as an example, it is 500°C or more and 680°C or less. The preferred second calcination temperature is, for example, 700°C or more and 850°C or less. It is preferred that there is a temperature difference of 50°C or more between each calcination process.

[0051] The roasting process is carried out by putting the above mixture into a roasting furnace. The roasting process may include a plurality of heating steps with different heating rates. For example, the temperature may be raised from room temperature to a first roasting temperature (first heating step) at a rate of 1.0°C / minute or more and 5.5°C / minute or less, and the temperature may be raised from the first roasting temperature to a second roasting temperature (second heating step) at a rate of 0.1°C / minute or more and 3.5°C / minute or less slower than the first heating step. The maximum reaching temperature of the roasting process may be maintained for a predetermined time (e.g., 1 hour or more and 10 hours or less).

[0052] In the following water washing step, the calcined product obtained in the calcining step is washed with water to remove impurities, and the washed calcined product is heated and dried. As needed, the calcined product is crushed, classified, etc., and the D50 of the positive electrode active material is adjusted to the target range. The calcined product after water washing can also be dried at a temperature of less than 100°C. An example of a preferred drying temperature is 150°C to 250°C. The drying process can be carried out both under vacuum and in the atmosphere. An example of the drying process time is 1 hour to 5 hours.

[0053] The composite oxide (Z) is obtained by precipitating (coprecipitating) a composite hydroxide containing Ni and any metal element and heat-treating the composite hydroxide. The composite hydroxide can be synthesized, for example, by adding an alkaline solution such as sodium hydroxide while stirring a solution of a metal salt containing Ni and any metal element (Co, Al, Mn, M2, etc.) and adjusting the pH to the alkaline side (for example, 8.5 or more and 12.5 or less). There is a tendency that the higher the pH during synthesis, the smaller the particle size of the composite hydroxide. In addition, the particle size of the composite hydroxide can also be controlled by adjusting the amount of solution of the added metal salt, for example, there is a tendency that the more the amount of solution, the larger the particle size. The particle size of the composite oxide (Z) can be adjusted, for example, by controlling the particle size of the precursor, i.e., the composite hydroxide. The heat treatment temperature is not particularly limited, for example, in the range of 250°C to 600°C.

[0054] [negative electrode]

[0055] The negative electrode 12 includes a negative electrode core 40 and a negative electrode mixture layer 41 disposed on the negative electrode core 40. The negative electrode core 40 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 41 includes a negative electrode active material and a binder, and is preferably disposed on both surfaces of the negative electrode core 40 except for the portion connected to the negative electrode lead 21. The negative electrode 12 may be manufactured, for example, by coating a negative electrode mixture slurry including a negative electrode active material and a binder on the surface of the negative electrode core 40, drying the coating, and then compressing the coating to form the negative electrode mixture layer 41 on both surfaces of the negative electrode core 40.

[0056] Similar to the case of the positive electrode 11, the binder contained in the negative electrode mixture layer 41 can also use fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., but preferably styrene-butadiene rubber (SBR) is used. In addition, the negative electrode mixture layer 41 preferably contains CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA) and the like. Among them, SBR is preferably used in combination with CMC or its salt, PAA or its salt. The content of the binder relative to the mass of the negative electrode mixture layer 41 is, for example, 0.1% by mass or more and 5% by mass or less. It should be noted that the negative electrode mixture layer 41 may also contain conductive additives such as CNT.

[0057] The negative electrode 12 may include a silicon-containing material having a particle expansion rate of 230% or less. The silicon-containing material is included in the negative electrode mixture layer 41 and functions as a negative electrode active material that absorbs and releases Li ions during charge and discharge of the battery. By using a silicon-containing material having a particle expansion rate of 230% or less as the negative electrode active material, the increase of the oxidative decomposition reaction on the negative electrode is suppressed, thereby improving the cycle characteristics of the battery. The particle expansion rate is controlled by, for example, the composition, particle size, shape, density, etc.

[0058] In a non-aqueous electrolyte secondary battery 10 in which at least one lithium transition metal composite oxide selected from the group consisting of Ca and Sr and at least one lithium transition metal composite oxide selected from the group consisting of W, Mo, Ti, Si, Nb and Zr exists at the interface between primary particles inside the secondary particles in the positive electrode 11, the cycle characteristics change significantly at a particle expansion rate of 230% of the silicon-containing material. When the particle expansion rate of the silicon-containing material is less than 230%, the cycle characteristics are significantly improved. This special effect occurs regardless of the content of the silicon-containing material, and is significant when the silicon-containing material is less than 20% by mass of the total mass of the negative electrode active material.

[0059] In this specification, the particle expansion rate of the silicon-containing material is measured by the following method.

[0060] (1) The battery to be evaluated was disassembled, the negative electrode plate was cut out, metal Li was used as the counter electrode, and an ionic liquid was used as the electrolyte to prepare a monopolar battery in which the cross section of the silicon-containing material particles was exposed.

[0061] (2) The monopolar battery was charged at 0.002 C in a temperature environment of 25° C. until the battery voltage reached 5 mV, and then discharged at 0.05 C until the battery voltage reached 1.0 V. The cross section of the silicon-containing material particles was observed in situ using a SEM.

[0062] (3) Based on the change in the cross-sectional area of ​​the silicon-containing material particles, the particle volume (V1) of the silicon-containing material in the charged state and the particle volume (V2) of the silicon-containing material in the discharged state are obtained, and the particle expansion ratio (V1×100 / V2) is calculated.

[0063] From the perspective of improving cycle characteristics, the particle expansion rate of the silicon-containing material can be 230% or less, but if the particle expansion rate is too small, the battery capacity tends to decrease. Therefore, the particle expansion rate of the silicon-containing material is preferably 150% or more. An example of a preferred range of the particle expansion rate is 150% or more and 230% or less. If the particle expansion rate of the silicon-containing material is within this range, it is easy to achieve both high capacity and excellent cycle characteristics.

[0064] As described above, the negative electrode mixture layer 41 contains a silicon-containing material as a negative electrode active material. Silicon-containing materials can absorb more Li ions than carbon-based active materials such as graphite that are usually used as negative electrode active materials. Therefore, by using silicon-containing materials, it is possible to achieve a high capacity of the battery. The negative electrode active material preferably also contains a carbon material. That is, the negative electrode mixture layer 41 may contain only a silicon-containing material as a negative electrode active material, but preferably contains a silicon-containing material and a carbon material.

[0065] The content of the silicon-containing material is preferably 3% by mass or more and 20% by mass or less of the total mass of the negative electrode active material. If the content of the silicon-containing material is within this range, it is easy to take into account both high capacity and high durability of the battery. In addition, the effect of using the composite oxide (Z) as the positive electrode active material becomes more significant.

[0066] The carbon material that functions as the negative electrode active material is, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon and hard carbon. Among them, as the carbon material, it is preferred to use at least artificial graphite such as blocky artificial graphite (MAG), graphitized mesophase carbon microbeads (MCMB), natural graphite such as flaky graphite, blocky graphite, and earthy graphite, or a mixture thereof. The volume-based D50 of the carbon material is, for example, 1 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less.

[0067] Soft carbon and hard carbon are classified as amorphous carbon with an underdeveloped graphite crystal structure. More specifically, it refers to a carbon component with a d(002) plane spacing of 0.342 nm or more based on X-ray diffraction. Soft carbon is also called easily graphitized carbon, which is carbon that is easier to graphitize by high-temperature treatment than hard carbon. Hard carbon is also called difficult to graphitize carbon. It should be noted that in the composition of the present invention, there is no need to clearly distinguish between soft carbon and hard carbon. As a negative electrode active material, graphite can also be used in combination with at least one amorphous carbon of soft carbon and hard carbon.

[0068] The silicon-containing material is a material containing Si, and as an example, silicon alloys, silicon compounds, and composite materials containing Si can be listed. Among them, composite materials containing Si are preferred. The D50 of the silicon-containing material is usually smaller than the D50 of graphite. The volume-based D50 of the silicon-containing material is, for example, greater than 1 μm and less than 20 μm or greater than 1 μm and less than 15 μm. It should be noted that the silicon-containing material can be used alone or in combination of two or more.

[0069] A preferred silicon-containing material (composite material) is a composite particle comprising an ion-conducting phase and a Si phase dispersed in the ion-conducting phase. The ion-conducting phase is, for example, at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase. The silicide phase is a phase of a compound composed of Si and an element more electropositive than Si, and as an example, NiSi, Mg2Si, TiSi2, etc. can be cited. The Si phase is formed by dispersing Si in fine particles. The ion-conducting phase is a continuous phase composed of a collection of particles finer than the Si phase.

[0070] The average value of the size (crystallite size) of the Si phase is preferably greater than 1 nm and less than 200 nm, more preferably greater than 1 nm and less than 50 nm. The average value of the size of the Si phase is calculated using the formula D = kλ / Bcosθ (k = 0.89, λ = 0.15418, 2θ = 28.4°, B is the half-height full width) and the half-height width of the diffraction peak (near 2θ = 28.4°) attributable to the Si (111) surface of the XRD pattern. The average size of the Si phase can be, for example, greater than 1 nm and less than 10 nm. By reducing the size of the Si phase, it is possible to maintain high capacity and suppress the particle expansion rate associated with charging and discharging.

[0071] The composite material may also have a conductive layer covering the surface of the ion conductive phase. The conductive layer is composed of a material with higher conductivity than the ion conductive layer, and forms a good conductive path in the negative electrode mixture layer 41. The conductive layer is, for example, a carbon coating composed of a conductive carbon material. The conductive carbon material may use carbon black such as acetylene black and Ketjen black, graphite, amorphous carbon (amorphous carbon) with low crystallinity, etc. Considering the conductivity and the diffusibility of Li ions into the interior of the particles, the thickness of the conductive layer is preferably more than 1 nm and less than 200 nm or more than 5 nm and less than 100 nm. The thickness of the conductive layer can be measured by observing the cross section of the composite material using SEM or a transmission electron microscope (TEM).

[0072] The ion-conducting phase may contain at least one element selected from the group consisting of Group 1 elements and Group 2 elements of the periodic table. The ion-conducting layer may be a silicon oxide phase doped with Li. In addition, the ion-conducting phase may also contain at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

[0073] An example of a preferred Si-containing composite material is a composite material having a sea-island structure in which fine Si is dispersed substantially uniformly in an amorphous silicon oxide phase and having a general formula of SiO xComposite particles represented by (0<x≤2). The main component of silicon oxide may be silicon dioxide. In addition, the silicon oxide phase may be doped with Li. The content ratio (x) of oxygen to Si is, for example, 0.5≤x<2.0, preferably 0.8≤x≤1.5.

[0074] Another example of a preferred composite material containing Si is a composite particle having a sea-island structure in which fine Si is dispersed approximately uniformly in an amorphous silicate phase. A preferred silicate phase is a lithium silicate phase containing Li. The lithium silicate phase is, for example, a general formula Li 2z SiO (2+z) The phase of the composite oxide represented by (0<z<2). Li4SiO4(Z=2) is preferably not included in the lithium silicate phase. Li4SiO4 is an unstable compound and is alkaline when reacting with water. Therefore, it sometimes deteriorates Si and causes a decrease in the charge and discharge capacity. From the perspective of stability, productivity, Li ion conductivity, etc., the lithium silicate phase preferably has Li2SiO3(Z=1) or Li2Si2O5(Z=1 / 2) as the main component.

[0075] Another example of a preferred composite material containing Si is a composite particle having a sea-island structure in which fine Si is roughly uniformly dispersed in a carbon phase. The carbon phase is preferably an amorphous carbon phase. The carbon phase may contain a crystalline phase component, but preferably contains more amorphous phase components. The composite material may contain particles of an amorphous carbon phase in which the ion-conducting phase is an amorphous carbon phase. The amorphous carbon phase is composed of, for example, a carbon material having an average plane spacing of greater than 0.34 nm in the (002) plane measured by X-ray diffraction. It should be noted that the composite material containing a carbon phase may have a conductive layer different from the carbon phase, or may not have the conductive layer.

[0076] [Separator]

[0077] The separator 13 can use a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be listed. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are preferred. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.

[0078] A filler layer containing an inorganic filler may be formed on the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0079] Example

[0080] Hereinafter, the present disclosure will be further described through examples, but the present disclosure is not limited to these examples.

[0081] <Example 1>

[0082] [Synthesis of lithium transition metal composite oxides]

[0083] A composite hydroxide containing Ni, Co, and Mn is synthesized by a coprecipitation method and heat-treated at 400° C. to obtain a composite oxide. The oxide, lithium hydroxide, calcium hydroxide as a raw material of the metal element M1, and niobium pentoxide and titanium oxide as raw materials of the metal raw material M2 are mixed so that the molar ratio of the metal element (Me) in the composite oxide to Li in the lithium hydroxide (Li / Me ratio) is 1:1.040.

[0084] The mixture was placed in a calcining furnace and calcined in three stages. During the calcination step, the mixture was calcined in an oxygen flow with an oxygen concentration of 95% (10 cm / s). 2 The mixture was heated from room temperature to 500°C at a heating rate of 2°C / min. The mixture was then heated from 500°C to 680°C at a heating rate of 1.5°C / min, calcined from 680°C to 750°C at a heating rate of 1°C / min, and then kept at 750°C for 3 hours. The calcined product was pulverized and washed with water, and then vacuum dried at 170°C to obtain a lithium transition metal composite oxide.

[0085] The obtained lithium transition metal composite oxide was analyzed by ICP-AES. As a result, the content of Ni was 89.9 mol%, the content of Co was 3.0 mol%, the content of Mn was 6.0 mol%, the content of Ca was 0.4 mol%, the content of Nb was 0.2 mol%, and the content of Ti was 0.5 mol% relative to the total amount of metal elements other than Li. In addition, the volume-based D50 of the composite oxide obtained by measuring with water as the dispersion medium using MT3000II manufactured by Microtrac Bell was 12 μm. By SEM images, it was confirmed that the composite oxide was a secondary particle formed by the aggregation of primary particles, and by TEM-EDX, it was confirmed that Ca, Nb and Ti were present on the surface of the primary particles.

[0086] [Production of positive electrode]

[0087] The above-mentioned lithium transition metal composite oxide is used as a positive electrode active material. The positive electrode active material, acetylene black and polyvinylidene fluoride (PVdF) are mixed at a solid content mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. The positive electrode mixture slurry is applied to both sides of a positive electrode core body composed of aluminum foil, and after the coating film is dried, the coating film is rolled using a roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer formed on both sides of the positive electrode core body. It should be noted that an exposed portion where the surface of the positive electrode core body is exposed is provided on a part of the positive electrode.

[0088] [Production of negative electrode]

[0089] Use SiO x A mixture of silicon-containing material and natural graphite shown as (0<x≤2) in a mass ratio of 3:97 is used as a negative electrode active material. A carbon coating is formed on the surface of the particles of the silicon-containing material. A dispersion of the negative electrode active material, sodium carboxymethyl cellulose (CMC-Na), and styrene-butadiene rubber (SBR) is mixed in a solid component mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode mixture slurry. The negative electrode mixture slurry is applied to both sides of a negative electrode core body composed of copper foil, and the coating film is dried and then rolled using a roller, and cut into a specified electrode size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode core body. It should be noted that an exposed portion where the surface of the negative electrode core body is exposed is provided on a part of the negative electrode.

[0090] [Preparation of non-aqueous electrolyte]

[0091] Ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4 (25° C.), and LiPF6 was dissolved in the obtained mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0092] [Fabrication of test battery (non-aqueous electrolyte secondary battery)]

[0093] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape through a polyolefin separator to prepare a wound electrode body. The electrode body is housed in a bottomed cylindrical outer can, the nonaqueous electrolyte is injected, and then the opening of the outer can is blocked with a sealing body to obtain a test battery.

[0094] <Example 2>

[0095] In the synthesis of lithium transition metal composite oxide, calcium hydroxide and strontium hydroxide were added as metal element M1 raw materials so that the Ca content was 0.3 mol% and the Sr content was 0.2 mol%. Zirconium oxide was added as metal element M2 so that the Zr content was 0.4 mol%. Other than this, the test battery was prepared in the same manner as in Example 1.

[0096] <Example 3>

[0097] In the synthesis of the lithium transition metal composite oxide, a test cell was prepared in the same manner as in Example 1, except that calcium hydroxide was added as the metal element M1 raw material so that the Ca content was 0.2 mol %, and tungsten oxide was added as the metal element M2 so that the W content was 0.4 mol %.

[0098] <Comparative Example 1>

[0099] A test cell was prepared in the same manner as in Example 1 except that the metal element M1 raw material and the metal element M2 raw material were not added during the synthesis of the lithium transition metal composite oxide.

[0100] <Example 4>

[0101] A composite hydroxide containing Ni, Co, Mn, and Al was synthesized by a coprecipitation method, and a heat treatment was performed at 400°C to obtain a composite oxide. In addition, calcium hydroxide was used as a raw material for the metal element M1, and niobium pentoxide and zirconium oxide were used as raw materials for the metal element M2. In addition, a mixture of the silicon-containing material used in Example 1 and natural graphite in a mass ratio of 6:94 was used as a negative electrode active material. Otherwise, a test cell was prepared in the same manner as in Example 1. It should be noted that the obtained lithium transition metal composite oxide was analyzed by ICP-AES, and the results showed that the content of Ni was 89.2 mol%, the content of Co was 3.0 mol%, the content of Mn was 6.0 mol%, the content of Al was 1.0 mol%, the content of Ca was 0.4 mol%, the content of Nb was 0.2 mol%, and the content of Zr was 0.2 mol%, relative to the total amount of metal elements other than Li.

[0102] <Example 5>

[0103] In the synthesis of the lithium transition metal composite oxide, a test cell was prepared in the same manner as in Example 4, except that calcium hydroxide was added as the metal element M1 raw material so that the Ca content was 0.3 mol % and zirconium oxide was added as the metal element M2 so that the Zr content was 0.4 mol %.

[0104] <Example 6>

[0105] In the synthesis of lithium transition metal composite oxides, calcium hydroxide and strontium hydroxide were added as metal element M1 raw materials so that the Ca content was 0.2 mol% and the Sr content was 0.1 mol%. Tungsten oxide was added as metal element M2 so that the W content was 0.4 mol%. Other than this, a test battery was prepared in the same manner as in Example 4.

[0106] <Comparative Example 2>

[0107] A test cell was prepared in the same manner as in Example 4 except that the metal element M1 raw material and the metal element M2 raw material were not added during the synthesis of the lithium transition metal composite oxide.

[0108] <Comparative Example 3>

[0109] A test cell was prepared in the same manner as in Example 5 except that the metal element M2 raw material was not added during the synthesis of the lithium transition metal composite oxide.

[0110] <Comparative Example 4>

[0111] A test cell was prepared in the same manner as in Example 5 except that the metal element M1 raw material was not added during the synthesis of the lithium transition metal composite oxide.

[0112] <Example 7>

[0113] A composite hydroxide containing Ni and Mn was synthesized by a coprecipitation method, and a heat treatment was performed at 400°C to obtain a composite oxide. In addition, calcium hydroxide was used as a raw material for the metal element M1, and niobium pentoxide and zirconium oxide were used as raw materials for the metal element M2. In addition, a mixture of the silicon-containing material used in Example 1 and natural graphite in a mass ratio of 20:80 was used as a negative electrode active material. Otherwise, a test cell was prepared in the same manner as in Example 1. It should be noted that the obtained lithium transition metal composite oxide was analyzed by ICP-AES, and the results showed that the content of Ni was 90.0 mol%, the content of Mn was 9.0 mol%, the content of Ca was 0.4 mol%, the content of Nb was 0.2 mol%, and the content of Zr was 0.4 mol%, relative to the total amount of metal elements other than Li.

[0114] <Example 8>

[0115] In the synthesis of lithium transition metal composite oxide, calcium hydroxide and strontium hydroxide are added as metal element M1 raw materials so that the Ca content is 0.4 mol% and the Sr content is 0.2 mol%. Tungsten oxide is added as metal element M2 so that the W content is 0.4 mol%. Except for this, the test battery is prepared in the same manner as Example 7.

[0116] <Comparative Example 5>

[0117] A test cell was prepared in the same manner as in Example 7 except that the metal element M1 raw material and the metal element M2 raw material were not added during the synthesis of the lithium transition metal composite oxide.

[0118] <Example 9>

[0119] A composite hydroxide containing Ni, Co and Mn is synthesized by a coprecipitation method, and a heat treatment is performed at 400°C to obtain a composite oxide. In addition, calcium hydroxide is used as a raw material for the metal element M1, and niobium pentoxide and zirconium oxide are used as raw materials for the metal element M2. In addition, only the silicon-containing material of Example 1 is used as the negative electrode active material. Otherwise, a test cell is made in the same manner as Example 1. It should be noted that the obtained lithium transition metal composite oxide is analyzed by ICP-AES, and the results show that the content of Ni is 90.2 mol%, the content of Co is 3.0 mol%, the content of Mn is 6.0 mol%, the content of Ca is 0.4 mol%, the content of Nb is 0.2 mol%, and the content of Zr is 0.2 mol%, relative to the total amount of metal elements other than Li.

[0120] <Example 10>

[0121] In the synthesis of lithium transition metal composite oxide, calcium hydroxide and strontium hydroxide were added as metal element M1 raw materials so that the Ca content was 0.4 mol% and the Sr content was 0.1 mol%. Zirconium oxide was added as metal element M2 so that the Zr content was 0.4 mol%. Except for this, the test battery was prepared in the same manner as Example 9.

[0122] <Comparative Example 6>

[0123] A test cell was prepared in the same manner as in Example 9 except that the metal element M1 raw material and the metal element M2 raw material were not added during the synthesis of the lithium transition metal composite oxide.

[0124] The capacity retention rate after the charge and discharge cycle of each test battery of the embodiment and the comparative example was calculated, and the evaluation results are shown in Tables 1 to 4, respectively. The evaluation results shown in Table 1 are relative values ​​when the values ​​of the test battery of Comparative Example 1 are set to 100. The evaluation results shown in Table 2 are relative values ​​when the values ​​of the test battery of Comparative Example 2 are set to 100. The evaluation results shown in Table 3 are relative values ​​when the values ​​of the test battery of Comparative Example 5 are set to 100. The evaluation results shown in Table 4 are relative values ​​when the values ​​of the test battery of Comparative Example 6 are set to 100.

[0125] [Measurement of Capacity Retention Rate (Evaluation of Cycle Characteristics)]

[0126] The test battery was charged at a constant current of 0.2 It at a temperature of 25°C until the battery voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current value reached 1 / 50 It. Then, the battery was discharged at a constant current of 0.2 It until the battery voltage reached 2.5 V. This charge and discharge cycle was repeated 100 times, and the discharge capacity of the 100th cycle was divided by the discharge capacity of the 1st cycle to obtain the capacity retention rate after the cycle test.

[0127] [Table 1]

[0128]

[0129] [Table 2]

[0130]

[0131] [Table 3]

[0132]

[0133] [Table 4]

[0134]

[0135] As shown in Tables 1 to 4, regardless of the proportion of the silicon-containing material in the negative electrode active material, the test battery of the embodiment has a higher capacity retention rate after the cycle test and excellent charge and discharge cycle characteristics than the test battery of the comparative example. It can be seen from Comparative Examples 3 and 4 that when only one of the metal elements M1 and M2 is added to the lithium transition metal composite oxide, the improvement effect of the cycle characteristics cannot be fully obtained. By adding the metal elements M1 and M2 at the same time, the cycle characteristics are significantly improved.

[0136] The present disclosure is further described through the following embodiments.

[0137] Option 1: A non-aqueous electrolyte secondary battery, comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode comprises a lithium transition metal composite oxide as a positive electrode active material, the lithium transition metal composite oxide having a layered structure and containing Ni of more than 75 mol% relative to the total molar amount of metal elements other than Li, the lithium transition metal composite oxide being secondary particles formed by aggregation of primary particles, at the interface between the primary particles inside the secondary particles, there is at least one selected from the group consisting of Ca and Sr and there is at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr, and the negative electrode contains a silicon-containing material as a negative electrode active material.

[0138] Scheme 2: The non-aqueous electrolyte secondary battery according to Scheme 1, wherein the lithium transition metal composite oxide is a general formula Lix Ni a Co b Mn c Al d M1 e M2 f O 2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0139] Aspect 3: The nonaqueous electrolyte secondary battery according to aspect 1 or 2, wherein at the interface between the primary particles inside the secondary particles, a particle of the general formula M1 is fixed α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

[0140] Aspect 4: The nonaqueous electrolyte secondary battery according to any one of aspects 1 to 3, wherein the negative electrode active material further includes a carbon material, and the carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.

[0141] Aspect 5: The nonaqueous electrolyte secondary battery according to aspect 4, wherein the content of the silicon-containing material is 3 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.

[0142] Option 6: A non-aqueous electrolyte secondary battery according to any one of Options 1 to 5, wherein the silicon-containing material comprises an ion conductive phase and a Si phase dispersed in the ion conductive phase, and the ion conductive phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase and a silicon oxide phase.

[0143] Aspect 7: The nonaqueous electrolyte secondary battery according to aspect 6, wherein the ion conductive phase contains at least one element selected from the group consisting of Group 1 elements and Group 2 elements of the periodic table.

[0144] Option 8: A non-aqueous electrolyte secondary battery according to Option 7, wherein the ion conductive phase further contains at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

[0145] Aspect 9: The nonaqueous electrolyte secondary battery according to any one of aspects 6 to 8, wherein the silicon-containing material includes particles of the carbon phase in which the ion-conductive phase is amorphous.

[0146] Description of Reference Numerals

[0147] 10 secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove part, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core, 31 positive electrode mixture layer, 40 negative electrode core, 41 negative electrode mixture layer

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium transition metal composite oxide as a positive electrode active material, the lithium transition metal composite oxide having a layered structure and containing 75 mol % or more of Ni relative to the total molar amount of metal elements other than Li, The lithium transition metal composite oxide is a secondary particle formed by aggregation of primary particles. At the interface between the primary particles inside the secondary particles, at least one selected from the group consisting of Ca and Sr and at least one selected from the group consisting of W, Mo, Ti, Si, Nb and Zr are present, The negative electrode contains a silicon-containing material as a negative electrode active material.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide is of the general formula Li x Ni a Co b Mn c Al d M1 e M2 f O 2-y The composite oxide shown in the formula, wherein 0.95<x<1.05, 0.75≤a≤0.95, 0≤b≤0.15, 0≤c≤0.25, 0≤d≤0.03, 0<e≤0.01, 0<f≤0.03, 0≤y<0.05, a+b+c+d+e+f=1, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein At the interface between the primary particles inside the secondary particles, a particle of the general formula M1 is fixed. α M2 β O γ The compound shown in the formula, wherein 1≤α≤2, 1≤β≤5, 4≤γ≤9, M1 is at least one element selected from the group consisting of Ca and Sr, and M2 is at least one element selected from the group consisting of W, Mo, Ti, Si, Nb and Zr.

4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The negative electrode active material further comprises a carbon material, The carbon material is at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, and hard carbon.

5. The nonaqueous electrolyte secondary battery according to claim 4, wherein The content of the silicon-containing material is 3 mass % or more and 20 mass % or less of the total mass of the negative electrode active material.

6. The nonaqueous electrolyte secondary battery according to claim 1, wherein The silicon-containing material comprises an ion-conducting phase and a Si phase dispersed in the ion-conducting phase, The ion-conducting phase is at least one selected from the group consisting of a silicate phase, a carbon phase, a silicide phase, and a silicon oxide phase.

7. The nonaqueous electrolyte secondary battery according to claim 6, wherein The ion conductive phase includes at least one element selected from the group consisting of Group 1 elements and Group 2 elements of the periodic table.

8. The nonaqueous electrolyte secondary battery according to claim 6, wherein The ion conductive phase contains at least one element selected from the group consisting of B, Al, Zr, Nb, Ta, V, La, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

9. The nonaqueous electrolyte secondary battery according to claim 6, wherein The silicon-containing material includes particles of the carbon phase in which the ion-conducting phase is amorphous.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2016143642A